2007
DOI: 10.1007/s11240-007-9238-z
|View full text |Cite
|
Sign up to set email alerts
|

Axillary proliferation and tuberisation of Dioscorea cayenensis–D. rotundata complex

Abstract: Yams (Dioscorea spp) are tuber crops used as staple food in Africa because of their nutritional value. However agronomic constraints, phytosanitary problems and the lack of good healthy planting material restrict their production. In contrast to the inefficiency of traditional method of planting, tissue culture techniques allow to increase the multiplication and the rapid production of pathogenfree plant material. This work was undertaken to provide farmers in African countries with healthy microplants and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…1a), resulting in the formation of one microtuber per explant as it was also previously described by Ondo Ovono et al (2007). During the following weeks, the size of the tuber increased.…”
Section: Discussionsupporting
confidence: 64%
“…1a), resulting in the formation of one microtuber per explant as it was also previously described by Ondo Ovono et al (2007). During the following weeks, the size of the tuber increased.…”
Section: Discussionsupporting
confidence: 64%
“…Ar: absorbing roots; Dr: dropper; Ne: necrotic explant; Sh: shoot; Swb: swollen buds; Rtu: root tubers and van Staden 1984;Sarkar 2008). There are several reports about in vitro formation of different storage organs in monocots, e.g., in Amaryllidaceae (Ilczuk et al 2005), Alliaceae (Goleniowski et al 2001), Araceae (Ndoumou et al 1995), Colchicaceae (Ghosh et al 2007), Dioscoreaceae (Sengupta et al 1984;Oyono et al 2007) and Zingiberaceae (Shirgurkar et al 2001). However, in spite of the great number of Orchidaceae that undergo this physiological phenomenon, there are very few reports of the promotion of storage organs in vitro in these species.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that microtubers could be obtained on yam nodal cutting explants, from an unique axillary bud, cultured in MS basal medium with or without plant growth regulators (Ondo Ovono et al 2007). The bud developed into a shoot and a weak enlargement at the base of the axillary bud was observed, resulting in the formation of a microtuber after 3 weeks on all the explants in control conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors are known to influence the tuberisation response in vitro. These may include day length (Vaillant et al 2005) and temperature (Grison 1991), the presence or absence of growth regulators either singly or in combination (Ondo Ovono et al 2007, or the presence of high sucrose (8%) concentration (Forsyth and Van Staden 1984).…”
Section: Introductionmentioning
confidence: 99%